Influence of zinc foliar spray on growth, some important physiological processes, yield and yield attributes of bread wheat under water stress - Hanan E. Ghanem; Doaa A. Hamza; A. A. Zain El-Abdeen; Walaa S. Elbatrawy; Helal M. El-Habashy (Scientific Reports)
Abstract Wheat constitutes one of the foremost important food crops in nations worldwide today. However, drought is one of the main global climate change risks that reduces agricultural productivity and causes significant economic losses. Zinc is an important nutritional microelement and is crucial for crops to be drought-tolerant. A field experiment was conducted at the Experimental Farm of Ismailia Agricultural Research Station, Egypt over two consecutive seasons under sprinkler irrigation to investigate the impact of various zinc levels (0, 100, 250, and 500 ppm) on Misr 3 wheat cultivar subjected to normal (100% field water capacity) and water stress (50% field water capacity) conditions. A split-plot design was used with three replicates, with irrigation treatments and zinc treatments allocated in separate main and sub-plots. Water stress was found to have a negative impact on shoot and flag leaf biomass, chlorophyll and carotenoids content, water relations and membrane characteristics. Also, drought significantly reduced yield and yield components. On the other hand, a gradual increase of Zinc up to a high level of 500 ppm alleviated water stress on wheat plants, thereby increasing the values of shoot fresh mass, shoot dry mass, flag leaf fresh mass, flag leaf dry mass, total chlorophyll, carotenoids, RWC, MSI and nutrient uptake. Moreover, all Zinc levels, especially 500 ppm, increased grain yield to 66.95–65.3%, yield attributes and the grain’s chemical composition (the relative content of wheat grain total protein, wet gluten, dry gluten and N P K Zn) under control and drought treatments. Therefore, foliar Zinc application, particularly at 500 ppm, can improve wheat plant growth, yield and grain nutrients beneath control and/or water stress conditions.